Survey of vertebrate diversity in forest fringe villages (Zoological Records and Reviews, 2023)
Forest fringe villages -- human settlements located immediately adjacent to or embedded within forest landscapes --occupy a critical interface between natural ecosystems and human land use, simultaneously harboring significantvertebrate diversity and representing nodes of human-wildlife conflict and biodiversity loss. Understanding the vertebratefauna of these interface zones is essential for designing conservation strategies that address both biodiversity protectionand the needs of forest-dependent communities. This study presents a comprehensive survey of vertebrate diversity --encompassing mammals, birds, reptiles, and amphibians -- in 36 forest fringe villages surrounding theNagarjunasagar-Srisailam Tiger Reserve (NSTR) in Andhra Pradesh and Telangana, India, using camera trapping, pointcounts, and visual encounter surveys over two years (2020-2022). A total of 342 vertebrate species are documentedacross four classes. Camera traps recorded 24 mammal species at village peripheries, including tigers, leopards, andsloth bears within 500 m of habitation. Bird diversity was highest at villages with large trees and traditional grain stores.Human-wildlife conflict incidents -- crop raiding by elephants, wild boar, and deer; livestock predation by carnivores;snakebite -- are documented at 28 of 36 villages. Forest cover loss rate within 2 km of surveyed villages is quantifiedfrom satellite data and correlated with vertebrate species richness decline. An integrated conservation-livelihoodframework for NSTR forest fringe villages is proposed.